Application of Electrical Resistivity Tomography for Cost-Effective Planning in Diabase Gravel Mining Operations in Southeastern Brazil - Lenon Melo Ilha; Cesar Augusto Moreira; Leonides Guirelli Neto; Henrique Masquelin; Ana Flavia da Silva Araújo; Luiza Lima Alves (Geofísica Internacional)
Planning in mineral extraction is fundamental to the operational and economic success of a mine, with an emphasis on reducing costs during exploration and the safety of operations. This study focused on small-scale mining operations to produce diabase gravel, an important input in civil building. The profile of residential construction in Brazil and other South American countries has historically depended on local materials such as sand, clay and stone. However, the operational viability of small-scale mines is closely linked to low-cost conditions, including soil thickness, rock homogeneity and water pumping costs. This study presents a case of using the geophysical method of electroresistivity, specifically electrical resistivity tomography, in a diabase gravel mining operation. Exploring deeper into the mine, the presence of granite was discovered at different depths, which implies various drilling, blasting and crushing costs. The distinction between diabase and granite, despite their similarities in electrical resistivity, is crucial for mine planning and project viability. The study overcame scientific and technological challenges, based on the geological/structural characteristics of each rock and on climatic and seasonal variables. The use of electrical resistivity tomography proved to be an effective solution, offering satisfactory results for mapping and discriminating between diabase and granite, providing crucial information for mine planning and potentially reducing operating costs. This work highlights the growing importance of applying geophysical methods to small-scale mining operations, as they can be an investigative technique to help with specific challenges faced by these operations.